ENVIRONMENTAL IMPACT ASSESSMENT UNDER AN ECOSYSTEM APPROACH: THE SÃO SEBASTIÃO HARBOR EXPANSION PROJECT - TURRA,ALEXANDER (2017)
Abstract The Environmental Impact Assessment (EIA) aims to analyze the environmental viability of projects, but exhibits problems that compromise its quality, such as the fragmented, technocratic and positivist vision. The prediction of environmental impacts can be improved using the ecosystem approach, considering the processes and the ecosystem services affected. The present work applied this approach in the expansion project of the Port of São Sebastião (São Paulo, Brazil), in which the EIA was judicially questioned, based on documental analysis and discussion by specialists. Unlike foreseen in the EIA, the analysis of oceanographic processes showed direct and indirect impacts on ecosystem services and benefits, irreversible and/or of great magnitude. The analysis also allowed an improvement to the comprehension not only on the effects on the environmental components and processes (hydrodynamics, sediment dynamics and biodiversity), but also on human well-being, evidencing the benefits of applying the ecosystem approach in the EIA.